Complete mitochondrial genome of the drywood termite Cryptotermes havilandi (Isoptera: Kalotermitidae) - Stiblik, Petr; Akama, Pierre Dieudonné; Šobotník, Jan (Mitochondrial DNA. Part B, Resources, 2021)
We report the first complete mitochondrial genome of an important pest of timber, the drywood termite Cryptotermes havilandi. The gene content and synteny of the mitochondrial genome of C. havilandi is identical to that of other termite species reported to date. It is composed 13 protein-coding genes, two ribosomal RNA genes, and 22 transfer RNA genes. Our phylogenetic tree, that includes the mitochondrial genomes of 14 species of Kalotermitidae, including C. havilandi, resolves the phylogenetic position of C. havilandi within Kalotermitidae.
Keywords: Kalotermitidae; termite mitochondrial genome; isoptera; drywood termites